Computational study of fin-equipped circular object on the cooling and power generation in an elastic-walled channel equipped with piezoelectric device - Selimefendigil, Fatih; Altammar, Hussain; Öztop, Hakan Fehmi (Elsevier, 2025)
Novel thermal management methods with energy storage and energy production mechanisms are preferred due to the need for effective cooling and energy efficient products. In this study, a novel system with fin-equipped circular object (FE-CO) is proposed with piezzo energy harvester (PEH) during turbulent forced convection hybrid nanofluid cooling of a hot block located in an elastic walled channel. The PEH is mounted below the elastic wall. Utilizing FEM and ALE, the numerical analysis takes into account a range of fin inclination values (y between 45 and 135), FE-CO horizontal location (xc between-0.35L and-0.23L), FE-CO vertical location (yc between 0.4H and 0.7H), fin size (Lf between 0 and 0.4H), and nanoparticle loading (cent between 0 and 0.03). It is shown that the fin length and position of the FE-CO are useful control parameters for PEH power generation and thermal management. Utilizing nanofluid results in a considerable boost in power generation as compared to using simply pure fluid. For nanofluid, the produced power increased by 14% between y = 45 and y = 75. From y = 75 to y = 135, the reduction amount is 53%. At y = 90, the biggest differences between pure fluid and nanofluid are observed for walls W1 (left vertical) and W3 (right vertical). For top wall W2, cooling performance improvement with nanofluid rises to 40%. By modifying the FE-CO's horizontal and vertical positioning with the use of nanofluid, the generated power enhancement factors become 13.8 and 3.8. While the produced power increases as the FE-CO's fin length increases, using nanofluid at the maximum fin length enhances cooling performance for hot wall components W1, W2, and W2 by around 75%, 13.5%, and 21%. The optimum values of (yc/H, y) when applying optimization are (0.444,97.7) for maximum cooling and (0.7,72) for greatest power generation. As compared to no object case, optimum case provides power enhancement factor of 17.8 while Nu increment becomes 36.5%
Keywords: Cylinder with fin; Piezoelectric; Thermal management; FEM; Ternary nanofluid